Sentidos familiares de la discapacidad: ¿narrativas discapacitantes?. (2019)
: This article presents some results of the research“Social representations of intellectual disability and its relation with the adaptive skills development in the communitylife”. Its main objective is comprehend the impact of socialbarriers in the human development through the analysis ofsocial expectations inside the group where an intellectuallydisable person is, and the way these expectations influencehis/her adaptive behavior. Based on some interviews, this article also takes special meanings that mothers have built upalong their experiences with an intellectual disabled person.